2004
DOI: 10.1111/j.1365-2621.2004.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 in the processing and post‐processing stages of acidophilus yogurt

Abstract: In this study the survival of Escherichia coli O157:H7 in the production process of acidophilus yogurt was examined and compared with traditional yogurt. Milk was inoculated with different doses of E. coli O157:H7 (10 2 , 10 4 and 10 6 CFU mL )1 ) and two kinds of yogurt were produced. Samples were taken for pH measurements and bacterial enumeration at 0, 3, 24, 48, and 72 h after inoculation. Escherichia coli O157:H7 was analysed by using a Most Probable Number technique and yogurt starter culture and Lactoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Our results are in accordance with those observed by Kasımoglu and Akgün (19) and Bachrouri et al (5) , who reported counts of E. coli O157:H7 increased about 1 log CFU mL -1 from initial inoculum during fermentation process. In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process.…”
Section: Resultssupporting
confidence: 93%
“…Our results are in accordance with those observed by Kasımoglu and Akgün (19) and Bachrouri et al (5) , who reported counts of E. coli O157:H7 increased about 1 log CFU mL -1 from initial inoculum during fermentation process. In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process.…”
Section: Resultssupporting
confidence: 93%
“…But no inhibition was observed against A. niger. This could be because the antifungal compound produced by the L. acidophilus could be specific in inhibiting C. neoformans but not A. niger (Jacobsen et al, 1999;Magnusson and Schnürer, 2002;Kastmoglu and Akgun 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The colony inhibitory effect of Lactobacillus on V. cholerae on TCBS agar plate is shown in (Figure 7 and 8 and Table 4) shows total number of colonies obtained in 10 -4 and 10 -6 dilution (Klaenhammer, 1983;Kastmoglu and Akgun, 2004;Alkaline et al, 2004).…”
Section: Colony Inhibitionmentioning
confidence: 99%
“…A sobrevivência de E. coli em iogurte é dependente de muitas variantes tais como o tipo de cepa, a dose do inoculo, o estágio de contaminação (pré ou pós-fermentação) e o tipo de bactéria ácido lática utilizado (5,11,18,19,21,22,23,26,27,31,32).…”
Section: Introductionunclassified